The Effectiveness of AI Based Blended Learning on Student Scientific Literacy: Meta-analysis - Abdul Rahman; Tomi Apra Santosa; Ilwandri Ilwandri; Yayat Suharyat; Sanju Aprilisia; Suhaimi Suhaimi (Badan Penerbit STIEPARI Press, 2023)
This study aims to analyze the effectiveness of blended learning based on artificial intelligence (AI) on students' science literacy. This type of research is called meta-analysis research. The data sources in the study came from 14 national and international journals published from 2018 to 2023. Data sources were searched through Google Scholar, ScienceDirect, Wiley, Eric, and ProQuest. Data source selection was carried out using the PRISMA method. Data sources have a relationship with the effectiveness of AI-based blended learning on students' science literacy. The data collection technique was direct observation through an online database. Data analysis used quantitative analysis with the help of the OpenMEE application. The results of this study showed that the AI-based blended learning model had a significant effect on students' science literacy. The effect size value is 0.93 with high criteria. This finding helps potential students improve their science literacy.